1993
DOI: 10.1111/j.1432-1033.1993.tb17910.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid‐receptor expression in human leukocytes

Abstract: Marijuana and many of its constituent cannabinoids influence the central nervous system (CNS), probably through the cannabinoid receptor, which has recently been cloned in rat and human. While numerous reports have also described effects of cannabinoids on the immune system, the observation of both mRNA and cannabinoid receptor has hitherto been exclusively confined to the brain, a reported detection in the testis being the sole example of its presence at the periphery. Here we report the expression of the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
205
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(215 citation statements)
references
References 40 publications
7
205
0
3
Order By: Relevance
“…Dual immunohistochemistry using pan-B cell markers confirmed previous observations that in general B lymphocytes are the leukocyte subsets expressing CB2 mRNA and protein (3)(4)(5) (Fig. 4).…”
Section: Figuresupporting
confidence: 69%
See 3 more Smart Citations
“…Dual immunohistochemistry using pan-B cell markers confirmed previous observations that in general B lymphocytes are the leukocyte subsets expressing CB2 mRNA and protein (3)(4)(5) (Fig. 4).…”
Section: Figuresupporting
confidence: 69%
“…The mechanism of activation appears to be a different one, because we neither found any increase of the CB2 protein levels, nor did the CB2 receptor activation status change following CD40 stimulation (data not shown). The peripheral cannabinoid receptor belongs to the family of seven-transmembrane GPCRs (3,4). GPCRs are crucial to many cellular functions, such as proliferation, maturation, survival, apoptosis, or migration (10 -12); Carayon et al (5) showed moderate proliferation of virgin and GC tonsillar B cells upon stimulation with the synthetic cannabinoid agonist CP55,940 only when the cells were stimulated with CD40 mAbs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…CB 2 receptor activation typically inhibits the functions of immune cells (reviewed in Parolaro, 1999), likely via the known CB 2 receptor intracellular signaling mechanisms: inhibition of adenylyl cyclase activity by G i/o proteins and activation of mitogenactivated protein kinase (Bouaboula et al, 1993;Bayewitch et al, 1995;Felder et al, 1995;Wartmann et al, 1995). The following subsections discuss in more detail the effects of endogenous, plant, and synthetic cannabinoid compounds on peripheral immune cells.…”
Section: Peripheral Cells Involved In Neuroinflammation Respond To Camentioning
confidence: 99%